Finite element investigation on the stress distribution and load transfer of cervical spinal motion segments after different stages of physiotherapy - Chan, Nicholas Kit Joo (2014)
The purpose of this project is to study the finite element investigation of stress experienced on neck after physiotherapy. X-ray images of day 1, day 7, day 16 and day 21 after physiotherapy were obtained to analyse the progression of the physiotherapy session.